Comparison of the Effectiveness of High Intensity Laser therapy (HILT) and Low-Level Laser Therapy (LLLT) on Functional Improvement in Knee Osteoarthritis Patients - Bernadete Rizky Natalia; I Made Widagda; Hari Peni Julianti (Medica Hospitalia : Journal of Clinical Medicine, 2024)
BACKGROUND : Knee osteoarthritis causes sore, joint stilted, progressive deformity and functional encroachment. The current therapeutic focus on rectifying function and assuaging symptoms, especially pain. There are two types of laser therapy, namely Low-Level Laser Therapy (LLLT) and High Intensity Laser Therapy (HILT). High Intensity Laser Therapy (HILT) is a high-intensity laser radiation with photochemical, photothermal, and photomechanical action possess many therapeutic steads including analgesic, anti-edematous, and biostimulating effects. In this study, we compare the effectiveness of HILT with LLLT on functional enhancement in knee osteoarthritis assessed by the Knee Injury and Osteoarthritis Outcome Score (KOOS). AIMS :  To compare the effectiveness of HILT with LLLT on functional enhancement in patients with knee osteoarthritis. METHOD : This research is a quasi-experimental  pre-test and post-test with controlled group design. There were 27 subjects of knee osteoarthritis patients who were divided into 2 treatment groups, the first treatment group admit HILT therapy (14 patients) and the second treatment group admit LLLT therapy (13 patients). Knee Injury and Osteoarthritis Outcome Score (KOOS) was measured before and after 4 weeks of treatment. RESULT :  There was a significant difference in the mean value of functional improvement as measured by KOOS before and after treatment in each group (p < 0.001) and there was a significant difference in the mean value of KOOS in the two groups (p < 0.001). CONCLUSION : The administration of HILT has shown significant escalation of functional improvement compared to the administration of LLLT in patients with knee osteoarthritis.